Beneath dark waters - Rose, Karen, 1964- (Rose, Karen, 1964- New Orleans novels, 2023)
"Deadly secrets lie beneath the murky waters of the Louisiana bayou in this pulse-pounding new romantic suspense novel from New York Times and USA Today bestselling author Karen Rose. There's no safe place for a child to hide when the danger comes from every direction. Public prosecutor J.P. "Kaj" Cardozo has lived in New Orleans for only six months, and he's already working on a high-profile celebrity sexual assault case that has made headlines all over the country. But when his son becomes the target of a kidnapping attempt as a threat to Kaj, he is desperate to keep him safe and turns to a private investigative firm famous for their protection services. A former marine, Val Sorensen is glad to have found a new career with Broussard Investigations, and her latest assignment as the bodyguard of ten-year-old Elijah Cardozo reminds her why: Val is a kick ass guardian with a tender heart. Through her duties, Val grows fond of the boy-and his handsome father. But when the high-stakes investigation reveals an explosive network of crime through a revived drug gang, lingering deep-seated corruption in the NOPD, and a group of murderers-for-hire targeting Kaj, Elijah, and Kaj's star client, they're all left scrambling for safety ..."--